2020
DOI: 10.1002/slct.202000809
|View full text |Cite
|
Sign up to set email alerts
|

Simple Chemical Modification Using Perfluoroalkyl‐Substituted Stable Nitrile N‐Oxide on Bulk Surface via Catalyst‐Free Click Reaction

Abstract: Fluorinated surfaces show favorable physical properties for material applications. However, fluorination processes of bulk surfaces using conventional reagents require skilled techniques and special equipment. Herein, we demonstrate highly efficient surface modification using a new fluorination tool, perfluoroalkyl‐substituted stable nitrile N‐oxide. The nitrile N‐oxide is successfully synthesized in one‐pot by exploiting 1,1‐diphenylnitroethene as the precursor of nitrile N‐oxide. The nitrile N‐oxide exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Moreover, the complete disappearance of the FTIR absorption signal at around 2291 cm –1 confirmed the full conversion of nitrile N -oxides (Figure S16). Compared with the reported conditions, , the reactions with allyltrimethylsilane of these nitrile N -oxides needed a shorter time and a lower temperature, indicating that such a −CNO group had a higher reactivity. It is concluded that the methyl group as the sterically hindered group had little influence on the reactivity of the aromatic −CNO group.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the complete disappearance of the FTIR absorption signal at around 2291 cm –1 confirmed the full conversion of nitrile N -oxides (Figure S16). Compared with the reported conditions, , the reactions with allyltrimethylsilane of these nitrile N -oxides needed a shorter time and a lower temperature, indicating that such a −CNO group had a higher reactivity. It is concluded that the methyl group as the sterically hindered group had little influence on the reactivity of the aromatic −CNO group.…”
Section: Resultsmentioning
confidence: 99%